2013
DOI: 10.3892/or.2013.2380
|View full text |Cite
|
Sign up to set email alerts
|

SDF-1-CXCR4 axis: Cell trafficking in the cancer stem cell niche of head and neck squamous cell carcinoma

Abstract: Stromal cell-derived factor-1α (SDF-1α), also known as CXCL12, has variable effects on a plurality of cells. CXCR4 has been identified as its corresponding receptor. The SDF-1-CXCR4 axis is postulated to be a crucial key pathway in the interaction between (cancer) stem cells and their surrounding supportive cells in the cancer stem cell niche. We evaluated the expression of CD44 as a cancer stem cell marker and of CXCR4 in human HNSCC tissue samples. Afterwards, we monitored the concentration of SDF-1 in perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…One such chemokine is the ubiquitous CXCL12 which signals via the chemokine receptors CXCR4. The CXCR4-CXCL12 signaling axis contributes to metastasis and clinical outcomes in many different types of solid cancer, including breast cancer [2833]. This receptor ligand pair appears to be involved in the directed migration of cancer cells to sites of metastasis, increased survival of cancer cells in sub-optimal conditions, and establishment of a tumor promoting cytokine/chemokine network.…”
Section: Discussionmentioning
confidence: 99%
“…One such chemokine is the ubiquitous CXCL12 which signals via the chemokine receptors CXCR4. The CXCR4-CXCL12 signaling axis contributes to metastasis and clinical outcomes in many different types of solid cancer, including breast cancer [2833]. This receptor ligand pair appears to be involved in the directed migration of cancer cells to sites of metastasis, increased survival of cancer cells in sub-optimal conditions, and establishment of a tumor promoting cytokine/chemokine network.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism in this work was not defined however they did report that the AHSG-associated migration activity of primary keratinocytes is largely independent of EGFR signaling and did not involve AKT1 or CDC42. However, Faber et al found that SDF-1α had great effect on migration in CD44þCXCR4þHNSCC cell lines [25, 26]. We recently showed that purified fetuin-A was a powerful chemo-attractant for breast and colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…74, 80 Overall, the presentation of critical signaling receptors at the cell surface reflects a series of dynamic processes including the rate of de novo synthesis, endocytosis, recycling and degradation. In particular, the decision point between recycling and degradation can markedly revise the net presentation of receptors at the cell surface and the longevity of receptor signaling.…”
Section: Introductionmentioning
confidence: 99%